Building a participatory methodological proposal for the development of the evaluation research: a contribution of the critical theory to the Social Service practice - da Silva e Silva, Maria Ozanira (Textos & Contextos (Porto Alegre), 2012)
The article, resulting from the teaching experiences in the field of social investigation, presents a methodological proposal, which is under construction to guide the development of the social investigation practice, with a focus on the evaluation of social policies and programs. It emphasizes relevant aspects of the methodological proposal under consideration, such as: the theoretical framework adopted; the concept of evaluation research used as a reference, followed by the illustration of the methodological proposal mediating the presentation of an experiment. In the experiment report, it seeks to demonstrate the potential of the methodological proposal adopted to favor spaces of collective thinking on social programs, professional practice and social reality. It also highlights the potential of participation for the development of a critical practice directed towards the social control of social policies and programs.